The Experiences of Syrian Female Students During the Distance Education and the Insights of Religious Culture and Ethics Teachers into the Process - İshak Tekin; Mustafa Fatih Ay (Cumhuriyet İlahiyat Dergisi)

(untitled)
Turkey has been hosting a large number of Syrian refugees since 2011 and has allowed Syrians to integrate into the general education system alongside Turkish students since 2016. This situation suggests that Turkey offers a unique experience in the education of Syrian refugees. However, Syrian girls may face disadvantages in their education due to traditional gender roles. Based on this premise, this study aims to examine the educational processes of Syrian girls during the COVID-19 pandemic from the perspectives of teachers, parents, and the students themselves. Therefore, this research seeks to identify the educational experiences of Syrian girls during the pandemic period in Turkey and to evaluate the contribution of religious culture and ethics (RCE) teachers to their ability to receive proper education. The participants of this research, which followed a qualitative design, included 10 students, 5 parents, and 5 RCE teachers selected through snowball sampling. The study's findings reveal that Syrian girls encountered difficulties in accessing and continuing distance education effectively. The data obtained were analyzed by considering the educational challenges experienced by refugee girls during the quarantine period from the perspectives of students, parents, and teachers, and discussed within psychological, social, and cultural contexts. Among these challenges, economic hardships, technical deficiencies, inadequacies in the physical environment, and social adjustment problems emerged as prominent issues. It was found that Syrian refugee girls struggled with limited financial resources, a lack of technological devices such as tablets and computers, inadequate internet access, and a shortage of appropriate learning environments. They also experienced psychological challenges, including isolation and a longing for social interaction, along with shifts in family dynamics. On the other hand, it was observed that Syrian girls and their parents frequently communicated with religious, cultural, and moral education teachers to address these issues. A significant finding that distinguishes this study from similar ones is that Syrian refugee girls, through their participation in both distance and face-to-face education, began to adapt to Turkish culture and lifestyle. According to the perspectives of both students and teachers, Syrian refugee students have become more socially integrated compared to their parents. As a result, it can be concluded that RCE teachers have assumed new, supportive roles in the education of Syrian refugee students.